1996
DOI: 10.1111/j.1365-2729.1996.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Groupwork and computers: task type and children's performance

Abstract: In the majority of British primary schools, children use the computer in groups of two or three. This is partly due to the lack of resources, that is, most classrooms still only have one or two computers to share between around 30 children. Groupwork on computers is also justified for pedagogic reasons. Previous research comparing children working in groups or alone has revealed an advantage for children working in groups although the work undertaken has generally been problem solving tasks. This investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Recent research into the use of educational ICT has focused primarily on social interaction and group work (Wild, 1996), student achievement levels (Jackson & Kutnick, 1996) and curriculum development. Very little study has focused upon promoting creative thinking through the use of online technologies, and this paper attempts to contribute to this area.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research into the use of educational ICT has focused primarily on social interaction and group work (Wild, 1996), student achievement levels (Jackson & Kutnick, 1996) and curriculum development. Very little study has focused upon promoting creative thinking through the use of online technologies, and this paper attempts to contribute to this area.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research on computer-based learning overwhelmingly reports the benefits of collaborative work as compared to individual work (Jackson & Kutnick, 1996;Johnson & Johnson, 1987). However, the effect of collaborative work on the acceptance of educational technology has not been studied before.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…A previous paper (Jackson & Kutnick, 1996) revealed that the type of task was crucial in determining whether groups were more successful than individuals in a computer‐based activity. A large body of research into computer‐based groupwork has demonstrated superior group performance as a robust effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, children, especially in the lower years of the primary school, engage in very little computer‐based problem solving, and simple practice and puzzle exercises predominate (DfEE, 1997). Using such a simple drill and practice task, Jackson and Kutnick (1996) demonstrated that infant school children working alone performed better than single sex pairs matched for ability. Thus, diverse task requirements require distinct groupings and relations (Wood & O'Malley, 1996; Howe, 1997).…”
Section: Introductionmentioning
confidence: 99%